Diversification and Garch volatility effect in investment portfolios - Chambi Condori, Pedro Pablo (2018)
Objective: To demonstrate the incidence of diversification in the reduction of stochastic volatility in an investment portfolio. Method: It is a Causal explanation and quantitative research that is based on the quantification and statistical analysis of financial time series of financial assets listed on the Lima Stock Exchange in the period 2014-2017. Results: The selected sample consisted of eight securities that are part of the Selective Index of the Lima Stock Exchange. Five investment portfolios have been organized with financial time series; the number of securities in each of these investment portfolios has been varied and recorded. Descriptive statistical analysis has been applied obtaining the expected return on investment and its GARCH volatility. Conclusions: In the structuring of investment portfolios, the theory of diversification has been applied as shown by the results on table 2. Applying the reduction effect of volatility is extremely important for placement agents and for stockbrokers since it contributes to the objective of minimizing risk and maximizing profitability. The techniques and quantitative tools available allow modeling, forecasting and simulations as well as optimization and determination of volatility models shown on table 4, which benefit all those involved in the optimal organization of investment portfolios.